International Student Mobility Goes Virtual : The e-EduTour - Soubakeavathi, Rethinasamy; Soo, Ruey Shing; Nurul Huzaimah, Hussien; Keezrawati, Mujan Yusuf; Liyana, Rosli; Joseph, Ramanair; Damien, Mikeng (RIEC, 2022)
The intense advancement in globalization in the past two decades has prompted the need for internationalization of higher education. Institutions of higher learning have realigned their approaches to include initiatives to develop their graduates’ global mindedness that would underpin their personal and professional lives. One of the strategies employed to meet this goal is through student mobility programmes which require experiences with host universities. However, the travel restrictions imposed due to the COVID-19 pandemic have affected the implementation of such programmes. This paper provides an illustration of the international student mobility programme called EduTour and describes its disruptive innovation journey from face-to-face to virtual. The new beyond normal e-EduTour utilized a hybrid approach and was successfully orchestrated virtually in 2021 and 2022. The uniqueness of the e-EduTour unfolded the opportunity for the creation of intellectual property (IP) followed by the commercialisation of the programme.